CONSUMER INSIGHT REMAJA PADA SEATING AREA CONVENIENCE STORE 7-ELEVEN - Jusuf Fadilah (Jurnal Komunikasi, 2016)
This study sought to determine consumer insight teenage consumers in seating area 7-Eleven convenience stores. While the research object is the 10 consumer teenagers hanging out at the 7-Eleven convenience stores. This study used a descriptive research design with qualitative approach, which is characterized by activities of collecting data and interpreting descriptive data about the situation experienced in order to explain the meaning corresponding to the phenomenon under study, through observation and interview approaches that focus on adolescent consumers who hang out at convenience stores 7-Eleven. Based on the findings obtained by the authors, this study found four categories of consumers teenagers who hang out at the 7-Eleven convenience stores, namely: Sevelgadget, Sevelita, Sevelholic and Sevelmix, where these categories represent of teenager who love to hang out in seating area 7-Eleven convenience stores. This research provides advice to consumers teenager who likes to hang out at the 7 -Eleven convenience stores to spend their time more wisely, also suggestions for the seating area providers, to better maintain and improve facilities and infrastructure seating area so consumers, especially consumers adolescents feel comfortable to spend time there.Keywords : Consumer Insight, Seating Area, Convenience Store 7-Eleven